2019
DOI: 10.1177/0886260519889942
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Norm in Acceptability Attitude of Women Toward Intimate Partner Violence in Punjab, Pakistan

Abstract: Intimate partner violence (IPV) is a public health and human rights issue with the social and economic impacts felt by women. Punjab is a male-dominated society, where partner violence is generally accepted as a cultural norm and viewed as normal behavior within a marriage. It stems from attitudes that partner violence is a private matter and usually a justifiable response to misbehavior on the part of the wife. The focus of the current study is to investigate the impact of this cultural norm in acceptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…At times, such behaviour is also justified on religious grounds [ 28 ]. It is consistent with a study of Pakistan which shows that intimate partner violence is considered as a private matter and usually a justifiable response to misbehaviour on the part of the wife [ 29 , 30 ]. Interestingly men are less likely to justify wife beating as compared to women in Pakistan [ 24 ] and women are considered wise if they remain obedient in tough situation particularly during inter-familial conflicts in rural areas [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…At times, such behaviour is also justified on religious grounds [ 28 ]. It is consistent with a study of Pakistan which shows that intimate partner violence is considered as a private matter and usually a justifiable response to misbehaviour on the part of the wife [ 29 , 30 ]. Interestingly men are less likely to justify wife beating as compared to women in Pakistan [ 24 ] and women are considered wise if they remain obedient in tough situation particularly during inter-familial conflicts in rural areas [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…There was significant variation in how these items were operationalized at the individual and group levels. For example, group-level aggregates ranged from the average number of items endorsed across individuals (Jesmin, 2015, 2017; Linos et al, 2013; Nadeem & Malik, 2019; Vyas & Heise, 2016), the proportion of individuals in the group that agreed with at least one scenario (Benebo et al, 2018; Cau, 2017; Cofie, 2020; Jesmin, 2015, 2017; Yount, Roof, et al, 2018), the proportion that agreed with all statements (Mogford & Lyons, 2014), the proportion that agreed with no statements (Kadengye et al, 2019), and various cut-offs based on the proportion of individuals agreeing with at least one statement (Ahmad et al, 2019; Antai & Adaji, 2012; Sandberg et al, 2018). The remaining studies used measures of attitudes toward female autonomy, men’s controlling behavior, and equitable and inequitable gender roles.…”
Section: Resultsmentioning
confidence: 99%
“…The 26 studies reviewed were international in scope, with 10 studies from sub-Saharan African (Antai & Adaji, 2012;Benebo et al, 2018;Cau, 2017;Cofie, 2020;Kadengye et al, 2019;Linos et al, 2013;Mulawa et al, 2018;Sandberg et al, 2018;Vyas & Heise, 2016;Weber et al, 2019), 10 from South Asia (Ahmad et al, 2019;Clark et al, 2018;Jesmin, 2015Jesmin, , 2017Koenig et al, 2003Koenig et al, , 2006Mogford & Lyons, 2014;Nadeem & Malik, 2019;Yount, James-Hawkins, et al, 2018;Yount, Roof, et al, 2018), one from East Asia (Kim & Emery, 2003), two from the Middle East and North African region (McCleary-Sills, 2013;Schuster et al, 2019), two from North America and western Europe (Beckmann et al, 2019;Copp et al, 2019), and one from Latin America (Shakya et al, 2016; see Table 1). Ever-partnered women aged 15-49 or 18-49 were the most studied population, with more than half of studies assessing outcomes among this population.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…While men may feel driven to demonstrate this power to both men and women, patriarchal societies’ deference to men and men’s opinions likely compels men to prioritize and internalize other men’s—as opposed to women’s—attitudes around masculinity and IPV. As such, this study highlights the importance of collecting and using attitudinal data from men, a practice that is not always prioritized when administering surveys related to IPV (Jesmin, 2015; Nadeem & Malik, 2019). In fact, BLINDED’s recent review of studies using norm proxies around IPV found that half of the included studies used reference groups comprised only of women (Seff, 2021).…”
Section: Discussionmentioning
confidence: 99%